Cervical Transforaminal Epidural Block Using Low‐Dose Local Anesthetic: A Prospective, Randomized, Double‐Blind Study. Issue 1 (7th October 2014) - Woo, Jae Hee; Park, Hahck Soo
Abstract Objectives Intra‐arterial injections of local anesthetic during cervical transforaminal epidural block (TFEB) can cause rare but fatal neurologic complications. We hypothesized that using a dose of local anesthetic lower than seizure threshold during cervical TFEB would not be associated with seizure activity in cases of accidental intra‐arterial injection. Methods Patients were randomized to one of two groups: group I received injections of 1 mL of 1% lidocaine mixed with dexamethasone 2.5 mg (n = 15), and group II received 1 mL of 0.125% lidocaine mixed with dexamethasone 2.5 mg (n = 15). When the numeric rating scale (NRS) for pain was greater than 3, cervical TFEBs were performed three times at 2‐week intervals. Patients were evaluated up to 3 months. Results Thirty patients with cervical radicular pain were enrolled in this study. The NRS pain score on the day of procedure and at 2 weeks, 4 weeks, 6 weeks, and 3 months following the initial procedure were similarly significantly reduced in both groups. The total number of procedures performed and the outcomes evaluated according to Odom's criteria at the 3‐month follow‐up visit were not different between groups. Overall, 73.3% and 80% patients in groups I and II, respectively, rated the degree of their symptom relief as excellent or good. Conclusion Cervical TFEB performed using 0.125% lidocaine with dexamethasone achieved similar satisfactory effects as 1% lidocaine with dexamethasone for the treatment of cervical radicular pain. Therefore, the use of low‐dose lidocaine with dexamethasone is reasonable for cervical TFEB, as this may reduce the incidence of rare but fatal complications.